2020
DOI: 10.3390/biom10091300
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Flavonoids Intake and Cognitive Function in an Italian Cohort

Abstract: Background: Diet is one of the leading factors contributing to the prevalence of non-communicable diseases, including neurodegenerative disorders. Dietary polyphenols, antioxidant components and anti-inflammatory agents of plant-based foods rich diets have been shown to modulate neuro-inflammation, adult neurogenesis and brain signaling, all of which are linked to cognitive function. As epidemiological evidence is limited and the results are contradictory, the aim of this study is to explore the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 51 publications
(49 reference statements)
1
34
0
Order By: Relevance
“…Among modifiable risk factors, dietary factors have been identified as playing a potential role in preserving and possibly improving mental health and cognitive status in older adults [ 5 ]. Recent scientific evidence demonstrated the beneficial effect of plant-based foods and beverages, rich in polyphenols [ 6 ], toward cognitive health, including fruits and vegetables [ 7 ]), nuts, whole grains and legumes [ 8 , 9 , 10 ], and coffee [ 11 ]. However, not only plant-based foods and/or manipulation of macronutrient intake have an effect; in fact nutritional interventions that consist of reducing global calories or increasing the fasting window between two meals have often been reported to improve healthspan and lifespan in a variety of organisms in laboratory settings, with increasing evidence that they are effective in humans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among modifiable risk factors, dietary factors have been identified as playing a potential role in preserving and possibly improving mental health and cognitive status in older adults [ 5 ]. Recent scientific evidence demonstrated the beneficial effect of plant-based foods and beverages, rich in polyphenols [ 6 ], toward cognitive health, including fruits and vegetables [ 7 ]), nuts, whole grains and legumes [ 8 , 9 , 10 ], and coffee [ 11 ]. However, not only plant-based foods and/or manipulation of macronutrient intake have an effect; in fact nutritional interventions that consist of reducing global calories or increasing the fasting window between two meals have often been reported to improve healthspan and lifespan in a variety of organisms in laboratory settings, with increasing evidence that they are effective in humans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also induce activation of anti-aging enzymes like sirtuin 1 [ 21 , 22 , 23 , 24 ] which together seem to constitute the key points of their anti-aging effects. In fact, recent evidence from observational studies demonstrated that higher intake of dietary polyphenols is associated with better cognitive function in adults [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study on 808 adults Italian cohort found that higher dietary intake of anthocyanins, flavan-3-ols, catechins, and flavonols are associated with better cognitive health [155]. Intake of dietary flavonoids can mitigate the pathogenesis of neurological disorders by reducing oxidative stress.…”
Section: Pre-clinical/clinical Studies Of Flavonoidsmentioning
confidence: 99%